Affordable housing livability attributes - Muhammad Muhir, Safira Nabilla; Ibrahim @ Atan Sipan, Fauziah Raji; Jaafar, Mohd Nadzri; Qutayan, Saleh Ba; Jiram, Wilson Rangga Anthony; Saimy, Intan Sazrina (2017)
Purpose - Housing plays an important role in people’s wellbeing, contributing to the physical and mental health, education, employment and security outcomes for individuals. Still, housing affordability has always been an issue worldwide. Governments have been scrambling to build sufficient affordable houses to meet the forever increasing demand. In light of this there is concern that the livability aspects of these affordable houses built have been compromised. For that reason, this study presents a research on the attributes of livable-affordable-homes. The findings indicated that there are seven significant affordable housing livability attributes.Methodology - Data was gathered by identifying all livable attributes from literature and previous research carried out with particular focus on Malaysia. A Focus Group Discussion was conducted to finalise and refine the attributes and sub-attributes of affordable-livable homes. The participatory organizations were picked based on their housing expertise and knowledge, which the researchers recognized as contributory towards the research according to the attributes identified. Findings - The aim of the FGD is to discuss and determine the attributes and sub-attributes of livable- affordable-homes.This discussion enables the researcher to gain a larger amount of information in a shorter period of time. Altogether 12 individuals representing related government bodies, public and private universities and NGOs participated.The findings indicated that there are seven significant affordable housing livability attributes namely physical factor, community and neighbourhood factor, public amenities, economic development, residence wellbeing, safety and security and also psychological impact.This research has taken into account of not only physical aspect but also psychological well being of the residents.